Intergenerational Collective Trauma: Analyzing the Psychosocial Crisis and Identity Formation Mechanisms among Post-Conflict Refugees in Poso - Donnye Rura Amping; Maria Goretti Adiyanti; Irene Ludji (Journal Psikologi Forensik Indonesia, 2025)
The prolonged conflict in Poso has left a lasting mark of collective trauma, particularly within refugee communities. This trauma has triggered a psychosocial crisis transmitted across generations through collective narratives, refugee identity, parenting styles, and socially embedded suspicion and prejudice. This study aims to explore the intergenerational transmission mechanisms of collective trauma among post-conflict refugees in Poso. Employing a qualitative case study approach and thematic analysis, in-depth interviews were conducted with two generational groups: direct survivors of the conflict and those born afterward. Findings reveal that trauma plays a significant role in identity formation among younger generations, reflected in high levels of anxiety, social withdrawal, and heightened sensitivity to violence. Social mechanisms such as “self-defense” and “self-counter” emerge as adaptive responses aimed at protecting community identity. These insights contribute to the design of more context-sensitive psychosocial interventions, including peace education, intergenerational parenting programs, and intercommunity safe spaces that foster reconciliation and integration.